A mensagem na música: estudos da teomusicologia sobre os cânticos dos Adventistas do Sétimo Dia - Mendonça, Joêzer de Souza [UNESP] (2014)
In the context of Christian music in Brazil, Adventists songs have effectively disseminated the theological message of the Seventh-day Adventist Church. The observation of Adventist musical field displays the connection between music and theology, in the sense that theological propositions for musical practice are related to the doctrinal distinction of Adventism. With the aid of Theomusicology, a methodological framework that consists in a theologically informed musicology, this study aims to verify if the theological mindset of Adventists is transferred to the structures of the composition of songs. The objective of this thesis is to introduce Theomusicology as a method of examining Christian song through the study of Adventist musical production